(untitled) (Phenomenology, Humanities and Sciences, 2023)
This article was guided by the following question: what is the role of art in language, truth, and poetry in the conception of philosopher Martin Heidegger? This question entails the need to answer it. Speaking of art as a moment of revelation of Being forces us to speak of the poet and poetic language, since art is intrinsic to human existence. The course followed by this work intends to clarify one of the most important reflections of philosopher Martin Heidegger: poetic language and the relationship between art and truth. The essay The Origin of the Work of Art (1935/36) was presented for the first time in mid-1935/36, a period during which seminars were given that fleshed out his work. Heidegger’s thinking about art and truth led the author to a new direction in his philosophy, one that brought him closer to Hölderlin’s poems. We will explore Heidegger’s encounter with the work of poet Hölderlin, which, for Heidegger, represents the path of thought linked to the sense of being, ultimately leading him to understand what poetic creation means.